FUNGI AND MACROFAUNA COMMUNITY IN POST-FIRE PEATLAND IN CENTRAL KALIMANTAN - Hakim, Safinah Surya; Halwany, Wawan; Rachmanadi, Dony (Association of Indonesian Forestry and Environment Researchers and Technicians, 2019)
Peat soil with its unique physical and chemical character is host to various microbe and fauna. In the peat, the existence of microbe and macrofauna influenced by several environmental parameters. Therefore, in this study we would like to obtain the information about fungi and macrofauna in the post fire degraded peat swamp soil with emphasize on two points which are (i) abundance of soil fungi and soil macrofauna (ii) to describe the environmental parameters (e.g. understory and chemical properties) on the existence of fungi and macrofauna community. Soil dilution and pitfall trap were used to collect microbes and macrofauna in the targeted post-fire peat soil: Post-fire peatland /bareland (A), post-fire peat-land revegetated in December 2016 (B), post-fire peat-land revegetated in April 2016 (C), post-fire peat-land revegetated in December 2015 (D). Result showed that abundance of soil fungi obtained during this study is 4×105 to 11×105 cfu/ml. While the macrofauna abundance is 353-1038 ind/m2. Fungi and macrofauna community in peatland affected by understory cover which related with revegetation activity. There is a trend of increasing the abundance of microbes and macrofauna on the land along with the increase of the percentage of understory cover.